PENERAPAN BIOTEKNOLOGI MIKROBA DAN PERANANNYA DALAM KEHIDUPAN DI LINGKUNGAN SEKOLAH SMA KABUPATEN BEKASI - Agus Utami, Annisa Wulan; Kurniati, Tri Handayani; Heryanti, Erna (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Negeri Jakarta, 2023)
Abstract Community empowerment in the Bekasi regency area is needed, one of which is through science and technology skills to face the progress of the 21st century. The rapid development of science and technology makes Biotechnology one of the fields of science that must be mastered by the Indonesian nation, including high school students. This is because, in addition to being directly related to everyday life, it can also be related to aspects of